2023
DOI: 10.3390/molecules28041834
|View full text |Cite
|
Sign up to set email alerts
|

Desert Endemic Plants in Algeria: A Review on Traditional Uses, Phytochemistry, Polyphenolic Compounds and Pharmacological Activities

Abstract: Due to their robust antioxidant capabilities, potential health benefits, wide variety of biological activities, and strong antioxidant qualities, phenolic compounds are substances that have drawn considerable attention in recent years. The main goal of the review is to draw attention to saharian Algerian medicinal plants and the determination of their bioactivity (antioxidant, anti-cancer, and anti-inflammatory importance), and to present their chemical composition as well as in vivo and in vitro studies, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 136 publications
(143 reference statements)
0
7
0
Order By: Relevance
“…Nowadays, many contemporary pharmaceutical roots could be found in the traditional medicine of different nations [ 57 ]. Although the pharmaceutical revolution has led to the synthesis of numerous new molecules, many significant novel medicines are expected to have natural origins and to be based on data from folk medicine [ 44 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, many contemporary pharmaceutical roots could be found in the traditional medicine of different nations [ 57 ]. Although the pharmaceutical revolution has led to the synthesis of numerous new molecules, many significant novel medicines are expected to have natural origins and to be based on data from folk medicine [ 44 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained are shown in Table 2. A large number of scientific studies demonstrate that the consumption of a polyphenol-rich diet helps reduce the risk of chronic diseases, with health benefits for the human body [18,19].…”
Section: Mycochemical Screeningmentioning
confidence: 99%
“…The projected potential for development is essentially unlimited due to the enormous contribution of medicinal plants to health care, economic income, cultural identity, and livelihood security. [15][16][17] Rosemary (Rosmarinus officinalis) is a widely distributed aromatic shrub with good market prospects due to its rich active ingredients that are widely used in the field of medicine, food preservation, cosmetic and other industries. [18][19][20][21] It has been demonstrated that rosemary EO has good antibacterial, antioxidant, anti-inflammatory and antitumor effects, [22,23] and is effective in alleviating depression and reducing the risk of Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Human research on medicinal plants has been uninterrupted, stemming from the important role they play in everyday life. The projected potential for development is essentially unlimited due to the enormous contribution of medicinal plants to health care, economic income, cultural identity, and livelihood security [15–17] . Rosemary ( Rosmarinus officinalis ) is a widely distributed aromatic shrub with good market prospects due to its rich active ingredients that are widely used in the field of medicine, food preservation, cosmetic and other industries [18–21] .…”
Section: Introductionmentioning
confidence: 99%